Dynamically stable sets in infinite strategy spaces - Norman, T (University of Oxford, 2005)
Evolutionary game theory has largely focused on finite games. Dynamic stability is harder to attain in infinite strategy spaces; Bomze (Monatshefte fur Mathematik 110, 1990, 189-206) and Oechssler and Riedel (Economic Theory 17, 2001, 141-162) provide conditions for the stability of rest points under the replicator dynamics. Here, conditions are given for the stability of sets of strategies under this process.